Exploring Tiktok's Impact on Enhancing Speaking Skills in Language Learning: A Classroom Action Research - Mujayanah, Sri; Maruf, Nirwanto; Asari, Slamet (Universitas PGRI Adi Buana Surabaya, 2023)
TikTok is one of the media used in the speaking study. Many benefits can be obtained in the TikTok application, especially to improve speaking abilities. This research aims to know the use of TikTok in language learning to improve students' speaking skills and identify the effect of applying TikTok as a learning platform. This study aims to shed light on the role of TikTok in enhancing students' speaking abilities. The method used is quantitative method with Classroom Action Research. CAR is carried out in TKR at SMK Wijaya Putra Surabaya. This study's results demonstrated the effectiveness of using TikTok in improving students' speaking skills. Implementing TikTok resulted in a significant increase in students' post-test scores compared to their pre-test scores. It indicates that TikTok positively influenced students' motivation and performance in speaking English. Throughout the research, students showed a positive attitude towards using TikTok as a learning tool. They enjoyed the new experiences and found the interactive nature of TikTok engaging. The evidence from this study supports the notion that TikTok effectively enhances students' speaking skills, as seen in the considerable improvement in their scores and positive attitude during the tests.